PRODUCT QUALITY CONTROL ANALYSIS HAPPY GEMBONG BREAD PRODUCTION IN SAMARINDA - Muhammad Aldy Satyadi, Elfreda Aplonia Lau, dan Umi Kulsum (Prodi Ilmu Administrasi Negara, 2020)
This research was conducted with the consideration that it is necessary todetect the occurrence of damaged products in Roti Gembung Happy inSamarinda. Is the defective product standard (4%) set by Roti GembongHappy Samarinda management smaller than the defect product standardbased on the Statistical Processing Control (SPC) method in the UpperControl Limit (UCL) and Lower Control Limit (LCL) control limits?The results of quality control can help management to maintainquality that is already well categorized, improve product quality in the eventof quality degradation. Likewise, quality control needs to be done to reducethe number of damaged goods, so that the efficiency of time, cost and energythat actually boosts revenue increases.The analytical tool used in this study is the Statistical ProcessingControl (SPC) upper control limit and lower control limit, as well as controltools such as check sheets, histograms, control maps, pareto diagrams, anddiagrams cause and effect.The results showed that the bread damage tolerance limit of 4%determined by Roti Gembung Happy Manager is smaller than the upper limitof quality control (Uper Control Limit) and the lower limit of quality control(Lower Control Limit) according to the calculation of the StatisticalProcessing Control method which indicates the need to do quality control atthe input, process and output stages.